Enhancing Coverage and Cost-effectiveness of Brazil’s Unemployment Protection System : Insights from International Experience - Morgandi, Matteo; Fietz, Katharina Maria; Ed, Malin Linnea Sofia; De Farias, Alison Rocha; Weber, Michael (World Bank, Washington, DC, 2021)
The objective of the policy note is to inform reforms of the unemployment protection system of Brazil,through a comparison of its salient features with international benchmarks, and by taking stock of employment dynamics since the 2014 crisis. Recommendations include varying degrees of ambition (and political complexity), from parametric reforms of the unemployment insurance Seguro Desemprego (SD) to more systemic reorganization of programs, and the extension of coverage to growing shares of nondependent workers. The note builds on prior analysis of Brazil’s labor market programs undertaken as part of the World Bank’s expenditure review for Brazil (published World Bank 2018). The main novelties include a broader and deeper international benchmarking, as well as analysis of the unemployment dynamics since 2015, which are important to inform the optimal redesign of unemployment programs. The note was developed before the COVID-19 pandemic, and, while it takes stock of recent trends, it is not meant to be an assessment of Brazil’s emergency response or do justice to the emerging literature and data on the matter. As Brazil prepares for its economic recovery, the note aims to provide valuable information for a national policy debate around the much-needed modernization of the unemployment protection system. The note is organized as follows. The first part of the note takes stock of some of the key characteristics of Brazil’s labor market and unemployment dynamics since the 2014 economic crisis using the National Household Sample Survey Pesquisa Nacional por Amostra de Domicílios Contínua (PNADc) survey data. The centerpiece of the analysis is the comparison of the design features of SD to a range of international programs of reference countries, through a benchmarking exercise of its regulation, generosity, activation measures, and effective coverage rate. The final part of this note summarizes the key findings and provides recommendations.